English grammar in use supplementary exercises with answers - Hashemi, Louise (Cambridge University Press, 1995)
This book contains 200 varied exercises to provide students with extra practice of the grammar they have studied in English Grammar in Use Third Edition. The ideal companion to English Grammar in Use, this book includes 200 additional exercises for extra practice of all the grammar covered in the main book. These supplementary exercises, with answers, are ideal for self-study.